ESTIMATION OF CARBON STORAGE IN WATER LETTUCE (Pistia stratiotes) AT FRESHWATER SWAMPS - Humaida, Nida; Krisdianto, Krisdianto; Peran, Setia Budi (The Journal is published by Graduate Programe of Lambung Mangkurat University, 2016)
This study was conducted in Banjar Regency, in the areas of Keraton, Keramat Baru, Tungkaran, Akar Baru and Sungai Tabuk villages, South Kalimantan, from April-July 2009. The purpose of the study was to estimate the amount of carbon storage in water lettuce (Pistia stratiotes) at freshwater swamps. The information obtained through this study is expected to provide benefits for the swampland management. The swamplands observed were the ones with water lettuce growing in the swamps. The sampling was carried out using purposive sampling technique with the consideration of grouping water lettuce’s distribution. The carbon storage measurement was performed by measuring biomass, organic carbon percentage in water lettuce, and total carbon storage in m2. The organic carbon was analyzed using Walkey & Black's Method. There were also analyses of crude fiber and ash in water lettuce. Data were then analyzed using descriptive statistics and hierarchical clusters. The carbon storage in water lettuce at freshwater swamps in Banjar Regency ranged between 64.07 – 237.75 g/m2. The average crude fiber ranged between 19.89 - 24.94 % and ash between 20.91 - 28.69%.